2017
DOI: 10.1002/aoc.3839
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐ Dithizone grafted onto magnetic nanoparticles and study of its catalyticactivity in C‐C and C‐N coupling reactions

Abstract: In this paper, we report a simple, facile and efficient method for the synthesis of Fe 3 O 4 /SiO 2 -DTZ-Pd. The immobilized palladium was an efficient catalyst without addition of phosphine ligands for Stille, Heck and N-arylation reactions. This method has some advantages such as high yields and easy work up of products.In addition, the catalyst can be recovered using a magnet and reused several times without significant loss of its catalytic activity. This catalyst was characterized by various physico-chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…As catalytic systems, supported palladium oxide particles as well as supported isolated palladium surface complexes were chosen. Palladium oxide particles immobilized on various supports are well known for their application in C–C coupling reactions and can be regarded as standard or reference systems. , Examples of catalysts with immobilized palladium complexes or molecular palladium species for the Heck coupling reaction already exist, but unfortunately most studies lack detailed experimental-based proposals concerning the mechanism and therefore the cause for the partly high activities. The recent finding of extraordinarily high catalytic activity of grafted Pd methyl complexes on silica for the selective conversion of aryl chlorides opens the possibility of such mechanistic investigations …”
Section: Introductionmentioning
confidence: 99%
“…As catalytic systems, supported palladium oxide particles as well as supported isolated palladium surface complexes were chosen. Palladium oxide particles immobilized on various supports are well known for their application in C–C coupling reactions and can be regarded as standard or reference systems. , Examples of catalysts with immobilized palladium complexes or molecular palladium species for the Heck coupling reaction already exist, but unfortunately most studies lack detailed experimental-based proposals concerning the mechanism and therefore the cause for the partly high activities. The recent finding of extraordinarily high catalytic activity of grafted Pd methyl complexes on silica for the selective conversion of aryl chlorides opens the possibility of such mechanistic investigations …”
Section: Introductionmentioning
confidence: 99%
“…A novel cage‐like Pd–Schiff base complex immobilized on Fe 3 O 4 as a reusable magnetic nanocatalyst is described. Initially, Fe 3 O 4 nanoparticles modified with CPTMS (Fe 3 O 4 @CPTMS MNPs) were prepared according to a reported procedure . In order to prepare Fe 3 O 4 @PTMS‐DETA MNPs, DETA was grafted on Fe 3 O 4 @CPTMS MNPs via substitution reaction of NH 2 with terminal Cl groups.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, Fe 3 O 4 magnetic nanoparticles (MNPs) have attracted great attention due to their intrinsic magnetic property, facile synthesis and being environmentally friendly . During past decades, a few studies of monometallic nanocrystals, supported on magnetic Fe 3 O 4 , have been reported offering promising results in the catalysis of C─C cross‐coupling reactions . Moreover, there are many reports of Pd complexes supported on the surface of MNPs, such as Pd@Fe 3 O 4 ‐NH 2 /starch, Pd@g‐C 3 N 4 ‐Fe‐GO, PdAu/Fe 3 O 4 , Fe 3 O 4 @SiO 2 /isoniazide/Pd, Fe 3 O 4 /bentonite‐Pd, Pd (0/II) /CS‐bigua@Fe 3 O 4 , Fe 2 O 3 @FLG@Pd 0 , Fe 3 O 4 @CA‐Pd, Fe 3 O 4 @SiO 2 ‐Pd, etc.…”
Section: Introductionmentioning
confidence: 99%
“…F I G U R E 4 8 Preparation of MNPs/SiO 2 -DTZ-Pd. Reprinted with permission from Ghorbani-Choghamarani et al [216] Copyright 2017 John Wiley and Sons In 2020, the Zhang group [219] successfully built Pd NPs stabilized on magnetic Fe 3 O 4 NPs coated with pectin as a natural polysaccharide (Fe 3 O 4 @pectin/Pd) catalyst (Figure 50). The pectin as a natural polysaccharide not only protected the magnetic NPs from aggregation but also acted as a bio-reductant for the reduction of Pd 2+ ions and in-situ formation of Pd NPs.…”
Section: Palladium Nanocatalystsmentioning
confidence: 99%
“…Preparation of MNPs/SiO 2 ‐DTZ‐Pd. Reprinted with permission from Ghorbani‐Choghamarani et al [ 216 ] Copyright 2017 John Wiley and Sons…”
Section: Other Metal Nanocatalystsmentioning
confidence: 99%